Dynamic modeling of natural gas quality within transport pipelines in presence of hydrogen injections. (1st January 2017) - Guandalini, Giulio; Colbertaldo, Paolo; Campanari, Stefano
Highlights: Alternative energy-based approach for natural gas grid modeling. Dynamic modeling of pressure and flows according to customer requirements. Local composition calculation and gas quality tracking performed. Analysis of delivered gas properties after hydrogen injection in a single pipe (case study). Abstract: In the near future, the natural gas grid could face an increasing share of alternative fuels (biomethane, hydrogen) injected in addition to the traditional mixture. Indeed, this pathway is particularly promising in order to reach environmental objectives of CO2 emissions reduction, in both thermal and electrical final uses. Biogas is already abundantly produced and could be easily upgraded to biomethane; hydrogen technologies are still under development, but they can help the exploitation of the increasing availability of renewable energy sources. A promising solution to problems due to unpredictable fluctuations of renewable energy production (in particular related to wind parks) or excess energy with respect to the load lies in hydrogen production by electrolysis and further injection in the natural gas grid. In this scenario, the effects on design and management of the transport infrastructure should be investigated, and the compliance with composition limits and quality constraints has to be analyzed in both stationary and dynamic operation, tracking the gas quality downstream the injection point of the alternative fuels. A model was developed to simulate the unsteady operation of a portion of the gas grid; with respect to traditional volume-based approaches, a novel energy-based approach is developed, including variable composition along the pipes and allowing to consider a given energy delivery to customers as a constraint. After the validation against available operational data, a case study considering concentrated realistic domestic and industrial offtakes is simulated. The effects of hydrogen injection, usually not considered in NG grid design and operation analyses, are investigated in terms of composition, flow rate and pressure profiles with comparison to the reference natural gas case. The analysis shows how imposed quality thresholds can be respected, although the effects on calorific value, Wobbe index and density are not negligible; results indicate that the allowed hydrogen fractions are limited and highly sensitive to the profile and size of the offtakes connected to the pipeline. The discussion also evidences the potential impact of hydrogen injection on gas metering and measurements errors.